2023
DOI: 10.3390/life13051075
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable Risk Factors and Preventative Strategies for Severe Retinopathy of Prematurity

Abstract: Severe ROP is characterized by the development of retinal fibrovascular proliferation that may progress to retinal detachment. The purpose of this report is to review five of the most common and well-studied perinatal and neonatal modifiable risk factors for the development of severe ROP. Hyperoxemia, hypoxia, and associated prolonged respiratory support are linked to the development of severe ROP. While there is a well-established association between clinical maternal chorioamnionitis and severe ROP, there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 181 publications
0
3
0
Order By: Relevance
“…Likely, additional risk factors may have played a role in these critically ill patients in promoting ROP progression. 29 The data in this interim analysis comprise only a part of the planned study sample size of 146 patients; therefore, a positive effect of CB-RBC transfusions in preventing ROP progression could not be conclusively assessed. Moreover, the number of patients evaluated prevented adjusting for any centerrelated variability, and possible confounders due to local practices could not be excluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likely, additional risk factors may have played a role in these critically ill patients in promoting ROP progression. 29 The data in this interim analysis comprise only a part of the planned study sample size of 146 patients; therefore, a positive effect of CB-RBC transfusions in preventing ROP progression could not be conclusively assessed. Moreover, the number of patients evaluated prevented adjusting for any centerrelated variability, and possible confounders due to local practices could not be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…7 Modifying conditions that exacerbate hyperoxia in the rst phase, or hypoxia in the second one, might reduce the risk for ROP development and progression. 29 Among modi able risk factors, research has focused on the role of RBC transfusions and premature exposure to the adult form of hemoglobin, which has lower oxygen a nity than HbF. Using continuous near-infrared spectroscopy (NIRS) monitoring, we previously showed that CB-RBC and A-RBC transfusions are associated with different kinetics of cerebral regional oxygen saturation (crSO2) and cerebral fraction of tissue oxygen extraction (cFTOE).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have explored risk factors for ROP to identify a way to screen for ROP early. Several perinatal (3) and postnatal factors, such as elevated maternal leukocyte count and clinical chorioamnionitis, have been associated with ROP, and the most common and well-studied perinatal and neonatal risk factors for the development of severe ROP are hyperoxemia, hypoxia, and prolonged respiratory support (4). The current screening criteria for ROP, birth weight (BW) and gestational age (GA), have high sensitivity but low speci city (5), and others use postnatal weight gain or insulin-like growth factor 1 (IGF-1) levels to screen for ROP.…”
Section: Introductionmentioning
confidence: 99%